ANALYSIS OF LANDCOVER CHANGE AND ITS TRAJECTORY IN SUB-SAHARAN WEST AFRICA - Ibrahim, Yahaya Zayyana; Sada, Aisha (FUDMA JOURNAL OF SCIENCES, 2021)
The study analysed land cover change and its trajectory in the study area using 300m CCI-land cover data for three epochs (2000, 2005 and 2010) respectively. Five sampling sites were selected and analysed land cover change trajectories. The findings show a continued decline in closed forest and sparse vegetation and increase in cropland; an indication of land degradation. This pattern of land cover change is accelerated by the increasing number of human populations which is estimated to be growing at the rate of 2-3% in Africa by the year 2100. This nature of population growth is expected to increase the size of croplands to support food security, which will exert more pressure on the ecosystem. However, the land cover trajectories presented in the five sampling points does not portray much changes. This can be attributed partly to the temporal extent of the study (15-years) and the spatial resolution of the data. Overall, the land cover change trajectories in the five sampling sites shows that the major changes in the land cover have been caused by human activities and to some extent natural climatic variations especially along the marginal areas, where the size of bare surface have increased. Therefore, there is a need to carry out a comprehensive land cover assessment at local level to ascertain the major local driving forces and biophysical drivers of land cover degradation in the study area